2019
DOI: 10.14710/jbs.27.2.137-149
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH ORIENTASI KEWIRAUSAHAAN, KNOWLEDGE MANAGEMENT, DAN STRATEGI KEMITRAAN TERHADAP KEUNGGULAN BERSAING SERTA IMPLIKASINYA PADA KINERJA PERUSAHAAN (Studi Pada UMKM Kerajinan Logam Kecamatan Cepogo Kabupaten Boyolali)

Abstract: This research was conducted to develop a model to analyze the effect of entrepreneurial orientation, knowledge management, strategic partnership to competitive advantage as well as its implications on the performance of the company. The research problem posed is a decrease in production value and investment value along with the increasing number of metal craft business units in Cepogo, Boyolali Regency. The purpose of this study was to determine and analyze the entrepreneurial background, knowledge management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
3
4
1
2
Order By: Relevance
“…It means that collaborative programs conducted by private universities in West Java so far do not bring better benefits for the universities. In terms of partnership strategy and competitive advantage relationship, the result contradicts with previous research by Ratnawati (2019), Herawaty andRaharja (2019), andMuchtar et al (2018).…”
Section: N P R E S Scontrasting
confidence: 95%
See 1 more Smart Citation
“…It means that collaborative programs conducted by private universities in West Java so far do not bring better benefits for the universities. In terms of partnership strategy and competitive advantage relationship, the result contradicts with previous research by Ratnawati (2019), Herawaty andRaharja (2019), andMuchtar et al (2018).…”
Section: N P R E S Scontrasting
confidence: 95%
“…Partnerships help to fulfill the desired conditions of these resources, which lead to competitive advantage (Ratnawati, 2019). Previous researchers have proven the effects of partnership strategy on competitive advantage (Ratnawati, 2019;Herawaty & Raharja, 2019;Muchtar, Miyasto, & Rahardja, 2018). The indicators to measure the partnership strategy is the agreement that universities partners focus on the efforts to gain high-quality university management, the partnership is based on long-term relationship, university leaders always find solutions to problems faced in operation, the universities and partners have continuous improvement partnership programs, and the universities always make planning and goal setting together with the partners.…”
Section: Introductionmentioning
confidence: 99%
“…This means that knowledge competence acts as a full mediation between entrepreneurial orientation and business performance. This result is in line with the results of Muchtar et al (2019), who found that the entrepreneurial orientation applied to companies has a significant positive effect on business performance through the mediation of knowledge competencies. Based on the explanation above, the formulation of the formed hypothesis is: Ha4: Entrepreneurial orientation has a positive effect on business performance through knowledge competence as a mediation variable.…”
Section: The Effect Of Business Competency On Business Performancesupporting
confidence: 91%
“…The Effect of Entrepreneurial Orientation on Business Performance through Knowledge Competence as a Mediation Variable Muchtar et al (2019) stated that management knowledge competence has an important relationship in entrepreneurial orientation to business performance, where knowledge competence is the main process in driving business performance by paying attention to entrepreneurial orientation. Acquisition of knowledge is the act of collecting, creating, taking, producing, storing and combining the application of knowledge competence in an entrepreneurial orientation so that it can be in line with business performance.…”
Section: The Effect Of Business Competency On Business Performancementioning
confidence: 99%
“…Proses menciptakan pengetahuan dalam organisasi akan berhasil jika terdapat interaksi antara tacit knowledge (pengetahuan internal yang ada pada diri karyawan) dan explicit knowledge (pengetahuan yang berada diluar diri karyawan) yang tercipta karena adanya proses sosialisasi, eksternalisasi, dan kombinasi serta internalisasi. Knowledge management dibutuhkan agar dapat mendukung dan mengembangkan praktik kerja dan kegiatan usaha supaya perusahaan dapat mencapai kinerja pemasaran yang unggul (Muchtar et al, 2019). Hal ini didukung oleh Firdaus (2018) melalui penelitiannya yang berhasil mengungkap adanya pengaruh positif knowledge management terhadap kinerja pemasaran.…”
Section: Pendahuluanunclassified